Study of the Frosting Factor Based on Finned-tube Heat Exchanger of Air-source Heat Pump - Han Xing; Fan Wei; Chen Jianbo; Chen Qiuhuo; Yao Jingshan (Zhileng xuebao)
The frost on the heat exchanger of air-source heat pump has a great influence on the operating performance. The frosting experiment based on a cascade type air-source heat pump water heater is carried out in the enthalpy-difference chamber in this paper, and the outdoor evaporator of the unit is a finned-tube heat exchanger. The experiment is conducted under the conditions that the outdoor temperature is from -18℃ to 6℃ and outdoor relative humidity is from 70% to 90%. Experimental results show that: First of all, the amount of frosting almost changes linearly with the frosting time which is of maximum in the outdoor temperature range of -3~3℃, and the lower outdoor temperature, the more frosting amount; Secondly, the outdoor relative humidity has a great influence on the quantity of frost, and the more humidity, the more frosting quantity; Finally, the frosting factor is proposed based on the relationships of the area and form of evaporator coil, the time of frosting, the difference of the dew point temperature and the temperature on the evaporator coil and the frosting quantity, and is from 6.51 to 10.31kg/(m2?℃?min) with the average value 8.58×10-4 kg/(m2?℃?min).